The impact of medical students’ attitudes towards group ethical norms on their academic achievement and classroom deviant behaviour: an empirical study from China - Zang, Zheng (Acta Bioethica, 2022)
In recent years, medical students’ absenteeism has been investigated in depth. Classroom deviant behavior is a richer concept than truancy behavior, but there are few researchers on this aspect in China. There are still many issues worth discussing about deviant classroom behavior. In this paper, questionnaires were given to 977 medical students to collect relevant data. After classifying the data, correlation analysis and multilevel linear regression analysis were used to conclude that academic performance and group ethical norms have a negative impact on medical students’ deviant behaviors in class. Group ethical norms have a significant positive influence on academic performance, and descriptive ethical norms and imperative ethical norms of group ethical norms have a significant influence on academic performance. The four dimensions of academic performance: academic performance, task performance, interpersonal promotion, and social comparison have a negative influence on medical students’ deviant behaviors in class. Descriptive ethical norms have an inverse effect on medical students’ deviant behaviors, while imperative ethical norms have no significant effect on deviant behaviors in class. Group ethical norms as a category of ethical norms clearly have significant implications for improving academic performance and reducing their transgressions in class. Reinforcing group ethics in medical students will not only contribute to their professional ethics upon graduation, but also to their academic performance.